2010
DOI: 10.1111/j.1750-3841.2010.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Tomato Juice Fermented with Bifidobacteria

Abstract: The objective of this research was to characterize the chemical properties of tomato juice fermented with bifidobacterial species. Tomato juice was prepared from fresh tomatoes and heated at 100 degrees C prior to fermentation. Bifidobacterium breve, Bifidobacterium longum, and Bifidobacterium infantis were inoculated in tomato juice and kept at 35 to 37 degrees C for up to 6 h. Fructooligosaccharide (FOS) was added to tomato juice prior to fermentation. The analyses for brix, total titratable acidity (TTA), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
3
19
0
1
Order By: Relevance
“…This difference was high for dried samples and ranged from 16.25% (genotypes S-60, SPRZ) to 19.05% (genotype SPSM). Koh et al (2010) found no statistical difference between fresh tomato and juice processed at 100 °C for 5 min, there was no statistically significant difference, which was in accordance with results of Sahlin et al (2004). They studied different ways of thermal processing of tomato and found that they did not impact the content of total dry matter weight.…”
Section: Dry Matter Weightsupporting
confidence: 76%
“…This difference was high for dried samples and ranged from 16.25% (genotypes S-60, SPRZ) to 19.05% (genotype SPSM). Koh et al (2010) found no statistical difference between fresh tomato and juice processed at 100 °C for 5 min, there was no statistically significant difference, which was in accordance with results of Sahlin et al (2004). They studied different ways of thermal processing of tomato and found that they did not impact the content of total dry matter weight.…”
Section: Dry Matter Weightsupporting
confidence: 76%
“…In addition to fiber contents, a significant amount of lycopene remained in the tomato cakes after the juice process. As compared with 11.3 ㎎/100 g lycopene previously determined in tomato juice (Koh et al 2010), approximately 83.6 ㎎/100 g (as dry basis) remained in the enzymetreated tomato cake. Therefore, enzyme-treated tomato cakes were considered a good source of fibers and lycopene.…”
Section: Resultsmentioning
confidence: 96%
“…The tomatoes were washed with tap water to remove soil and other impurities, dried at room temperature prior to use, and treated with steam for 3 to 4 min for easy peeling. The tomato fruits were ground and filtered through a pulper (AG-5500, Angel Juicer Co, Pusan, South Korea) with a sieve (0.8~1.1 ㎜ pore size) to separate tomato juice and cake containing peel and seed (Koh et al 2010). The tomato cake was homogenized using a D-500 homogenizer (Wiggen Hauser, Berlin, Germany) for 1 min.…”
Section: Preparation and Analysis Of Enzyme-treated Tomato Cakementioning
confidence: 99%
See 1 more Smart Citation
“…Lycopene was extracted from the cherry tomato powder and calculated based on a standard curve generated by a lycopene standard (Sigma, St Louis, MO, USA) (Koh et al, 2010).…”
Section: Preparation and Analysis Of Tomato Samplesmentioning
confidence: 99%